Morphological and Molecular Cytogenetic Characteristics of Giant Human Oocyte - Petrushko, Maryna; Buderatska, Natalia; Gontar, Yulia; Yurchuk, Taisiia (Cytology and Genetics, 2021)
The expedience of using oocytes with morphological dysmorphism in assisted reproduction tech- nology programs is debatable. This study aimed to estimate morphological and molecular cytogenetic char- acteristics of enlarged oocytes and to predict results of their further fertilization. Among 774 oocytes retrieved from 80 patients, 83 (11%) cells were enlarged. Morphometric analysis showed the diameter of the ooplasm to be (176.67 ± 1.76) μm and the diameter with ZP (200.8 ± 4.24) μm. Among these giant oocytes, 47 (56.6%) were at the metaphase II stage, 26 (31.3%) at the metaphase I stage, and 10 (12.1%) at the prophase I stage. The retrieved giant oocytes were characterized by dysmorphism of endo- and exocytoplasmic structures. Among 47 cells at the metaphase II stage, 40 (85.1%) oocytes had two polar bodies, three (6.4%) oocytes had one polar body, and four (8.5%) oocytes had a fragmented polar body. The assessment of the presence of mei- otic spindle by polarization microscopy showed that 39 (83%) oocytes had two meiotic spindles, 3 (6.4%) oocytes had one meiotic spindle, and 5 oocytes (10.6%) had no visualized meiotic spindles despite the pres- ence of polar bodies. After fertilization of 47 oocytes at the metaphase II stage, pronuclei were detected in 42 (89.4%) cells, including 9 (21.4%) oocytes with two pronuclei, 27 (63.3%) oocytes with 3 pronuclei, and 6 (15.3%) oocytes with four pronuclei. The molecular cytogenetic analysis demonstrated that the embryos obtained after fertilization of giant oocytes had a polyploid chromosome set number. Thus, the results of our study showed the inexpediency of using giant oocytes for further fertilization.
Keywords: oocytes; giant oocytes; morphological characteristics; molecular cytogenetic analysis